Identification of novel Lynch syndrome mutations in Chinese patients with endometriod endometrial cancer - Caixia Ren; Yan Liu; Yuxiang Wang; Yan Tang; Yawei Wei; Congrong Liu; Hongquan Zhang (Cancer Biology & Medicine, 2020)
Objective: Lynch syndrome (LS) predisposes patients to early onset endometrioid endometrial cancer (EEC). However, little is known about LS-related EEC in the Chinese population. The aim of this study was to investigate the prevalence of LS and to identify the specific variants of LS in Chinese patients with EEC. Methods: We applied universal immunohistochemistry screening to detect the expression of mismatch repair (MMR) proteins, which was followed by MLH1 methylation analysis to identify suspected LS cases, next-generation sequencing (NGS) to confirm LS, and microsatellite instability (MSI) analysis to verify LS. Results: We collected 211 samples with EEC. Twenty-seven (27/211, 12.8%) EEC cases had a loss of MMR protein expression. After MLH1 methylation analysis, 16 EEC cases were suggested to be associated with LS. Finally, through NGS and MSI analysis, we determined that 10 EEC (10/209, 4.78%) cases were associated with LS. Among those cases, 3 unreported mutations (1 frameshift and 2 nonsense) were identified. MSH6 c.597_597delC, found in 4 patients, is likely to be a founder mutation in China. Conclusions: We demonstrated the feasibility of a process for LS screening in Chinese patients with EEC, by using universal immunohistochemistry screening followed by MLH1 methylation analysis and confirmation through NGS and MSI analysis. The novel mutations identified in this study expand knowledge of LS.